The Impact of Renewable Energy Consumption on GDP and the Three Key Economic Sectors’ Growth in Malaysia - Ng, Sze May; Chin, Mui Yin; Chong, Christine Siew PYng; Foo, Lee Peng (International Journal of Economics and Financial Issues, 2025)
Despite Malaysia’s long-standing efforts to diversify its energy sources and increase renewable energy consumption since 1980, the progress has been hindered by inefficiencies and technological limitations, while the economic impact of these changes remains unmeasured. This study, using annual World Bank data from 1990 to 2022, examines the relationship and impact of renewable energy consumption on Malaysia’s economic and industry, service, and agriculture sectors’ growth. The findings suggest that the renewable energy sector is cointegrated and has a significant positive impact on the overall economy, and the industry and service sectors in the long run. Furthermore, the Granger causality Wald test results support the growth, neutrality, and conservation hypotheses for the overall economy, industry, agriculture, and service sectors, respectively, in the short run. Overall, the results suggest that renewable energy could benefit Malaysia’s economy in varying degrees across the three important sectors. Therefore, prioritizing investments in renewable energy consumption within the industry and service sectors is crucial, as they offer the largest positive impact on economic growth. Additionally, the adoption of technologies in agricultural sector is low, thus efforts to enhance access to modern farming techniques using renewable energy should be promoted to improve the performance of the agricultural sector.